Luminosity loss due to beam distortion and the beam-beam instability - Wu, J; Raubenheimer, T; Chao, A; Seryi, A; Sramek, C (2005)
In a linear collider, sources of emittance dilution such as transverse wakefields or dispersive errors will couple the vertical phase space to the longitudinal position within the beam (the so-called 'banana effect'). When the Intersection Point (IP) disruption parameter is large, these beam distortions will be amplified by a single bunch kink instability which will lead to luminosity loss. We study this phenomena both analytically using linear theory and via numerical simulation. In particular, we examine the dependence of the luminosity loss on the wavelength of the beam distortions and the disruption parameter. This analysis may prove useful when optimizing the vertical disruption parameter for luminosity operation with given beam distortions. © 2005 IEEE.